EFEKTIVITAS PELAKSANAAN QUALITY CONTROL BAGIAN PRODUKSI HERDA CAFÉ PUGER JEMBER - Febriyanti, Eka Dwi; Budi Satoto, Eko; Izzudin, Ahmad (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2023)
The purpose of this study was to determine the effectiveness of both the process and how to improve quality control at Herda Cafe Puger Jember. This type of research is qualitative research with the Sig Sixma method of descriptive analysis, in which data is collected through observation and documentation. Quantitative data is obtained from documents or archives in the production and personnel departments. Meanwhile, qualitative data were obtained from interviews and direct observation at the company. The sample used in this study is from the internal side, namely sales data and production defects or failures at Herda Cafe Puger Jember with MS application tools. Excel version 2019 This research uses various methods, namely define, measure, analyze, improve, and control, so as to produce DPMO values and six sigma values, with the highest DPMO value of 1,065,814 and a Sigma level value of 4.6 σ with a value of 15–25% range sales as a measure of failure in six sigma, which shows the damage of a product in one million items produced.